2017
DOI: 10.1155/2017/1096980
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoma-Derived Growth Factor Secreted from Mesenchymal Stem Cells Reduces Myocardial Ischemia-Reperfusion Injury

Abstract: Objectives The present study aimed to explore the major factors that account for the beneficial effects of mesenchymal stem cells (MSCs). Methods Using isobaric tags for relative and absolute quantitation method, hepatoma-derived growth factor (HDGF) was identified as an important factor secreted by MSCs, but not by cardiac fibroblasts (CFs). The protective effects of conditioned medium (CdM) from MSCs or CFs were tested by using either H9C2 cells that were exposed by hypoxia-reoxygenation (H/R) insult or an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Vivar et al [38] studied IR injury-induced death and the protective effect of insulin-like growth factor 1 in cultured neonatal rat cardiac fibroblasts. Zhou et al [39,40] established a model of cultured rat neonatal and adult cardiac fibroblasts, in which they have considered the deleterious effects of hypoxia and reperfusion, comparing biochemical and morphological changes in cultured fibroblasts to those of cultured ventricular myocytes [39]. They also found that conditioned media from cultured cardiac fibroblasts subjected to hypoxia and reoxygenation did not protect cardiac myocytes from IR damage, while factors from other non-myocytes of mesenchymal origin did [40]; however, these authors did not consider IR injury beyond changes associated with fibroblast death, or IPC, in their model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vivar et al [38] studied IR injury-induced death and the protective effect of insulin-like growth factor 1 in cultured neonatal rat cardiac fibroblasts. Zhou et al [39,40] established a model of cultured rat neonatal and adult cardiac fibroblasts, in which they have considered the deleterious effects of hypoxia and reperfusion, comparing biochemical and morphological changes in cultured fibroblasts to those of cultured ventricular myocytes [39]. They also found that conditioned media from cultured cardiac fibroblasts subjected to hypoxia and reoxygenation did not protect cardiac myocytes from IR damage, while factors from other non-myocytes of mesenchymal origin did [40]; however, these authors did not consider IR injury beyond changes associated with fibroblast death, or IPC, in their model.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al [39,40] established a model of cultured rat neonatal and adult cardiac fibroblasts, in which they have considered the deleterious effects of hypoxia and reperfusion, comparing biochemical and morphological changes in cultured fibroblasts to those of cultured ventricular myocytes [39]. They also found that conditioned media from cultured cardiac fibroblasts subjected to hypoxia and reoxygenation did not protect cardiac myocytes from IR damage, while factors from other non-myocytes of mesenchymal origin did [40]; however, these authors did not consider IR injury beyond changes associated with fibroblast death, or IPC, in their model. Lefort et al [41] reported that cultured human ventricular fibroblasts produced secretomes in response to 5 h of hypoxia and 24 h reoxygenation, which reduced cardiac myocyte death during the hypoxia/ reoxygenation challenge.…”
Section: Discussionmentioning
confidence: 99%
“…So, it is urgent need for finding novel therapeutic strategies. Mesenchymal stromal cell (MSC)-based therapy is a promising approach following I/R injury ( 2 , 3 ). Different mechanisms are associated with this therapy, such as anti-apoptosis, anti-inflammation, and proangiogenesis ( 4 ).…”
Section: Introductionmentioning
confidence: 99%